Predicting Suicidal Thoughts Through Defensive Mechanisms and Psychopathic Traits in Addicted Women - Sadeghi Nia, Kimia; Asmaee Majd, Sirvan (Psychology of Woman Journal, 2024)
Objective: The present study aimed to predict suicidal thoughts through defensive mechanisms and psychopathic traits in addicted women. Materials and Methods: The design of the current research was a correlational study using regression analysis. The sample included 150 addicted women from detoxification camps in Gilan Province, who were selected based on the inclusion criteria using convenience sampling. Three questionnaires were utilized in this study: the Defense Style Questionnaire (DSQ-40), the Beck Scale for Suicide Ideation (BSSI), and the Levenson Self-Report Psychopathy Scale (LSRP). The collected data were analyzed using Pearson correlation coefficients and multiple regression with SPSS-26 software. Findings: Correlation coefficients indicate significant associations between mature defensive style and suicidal thoughts (correlation coefficient: .37), mature style (.39), neurotic (.35), primary psychopathic traits (.40), and secondary traits (.54) (P<.01). Conclusion: Based on the results of this study, it is recommended that therapists and counselors working with addicted individuals pay attention to defensive mechanisms, suicidal thoughts, and psychopathic traits in addicted women, as awareness of these variables can assist in providing better and more appropriate services to these patients.